A prospective study of faecal immunochemical testing following polypectomy in a colorectal cancer screening population. Issue 4 (4th November 2017) - Gibson, David J; Nolan, Blathnaid; Rea, Joanna; Buckley, Maire; Horgan, Gareth; Sheahan, Kieran; Doherty, Glen A; O'Donoghue, Diarmuid; Mulcahy, Hugh E; Smith, Alan; Cullen, Garret
Abstract : Introduction: 52% of faecal immunohistochemistry test (FIT)-positive clients in the Irish National Colorectal Cancer Screening Programme (BowelScreen) have adenomatous polyps identified at colonoscopy in round 1. Although it is known that advanced adenomas and cancers cause an elevated FIT, it is not known if small (<5 mm) adenomas cause a positive FIT. Aims: Determine if removal of small polyps in an FIT-based colorectal cancer (CRC) screening programme is associated with a negative FIT on follow-up. Methods: A single-centre prospective observational study of consecutive participants attending for first round screening colonoscopy who had a positive FIT (>45 µg Hb/g) as part of the Irish Colorectal Cancer Screening Programme. Subjects were consented at the time of colonoscopy and were sent a repeat FIT 4–6 weeks later. Precolonoscopy and postcolonoscopy FITs were compared and correlated with clinical findings and endoscopic intervention. Results: 112 consecutive first round participants were recruited. Eight (7%) had cancer, 75 (67%) adenomatous polyps, 17 (15%) a normal colonoscopy and 12 (11%) other pathology. There was a clear difference in median FIT levels between the four groups (P=0.006). Advanced pathology (tumour or adenomatous polyp >1 cm) was associated with higher FIT than non-advanced pathology (median FIT 346 vs 89 P=0.0003). 83% (86/104) of subjects completed a follow-up FIT. Follow-up FIT remained positive in 20% (17/86). Polypectomy was associated with a reduction in FIT from a median of 100 to 5 µg Hb/g (P<0.0001). Removal of polyps >5 mm was the only factor independently associated with a negative follow-up FIT on multivariate analysis (OR 3.9 (1.3–11.9, P=0.04)). Conclusion: FIT is a sensitive test and levels increase with advanced colonic pathology. Polypectomy of advanced adenomas is associated with a negative follow-up FIT. However, alternative causes for a positive FIT should be considered in patients who have adenomas less than 5 mm detected or a normal colonoscopy.